Sistem Ekonomi Makro menurut Abu Yusuf - Musaiyana Musaiyana; Yadi Janwari; Dedah Jubaedah (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2025)
Abu Yusuf's thoughts on the macroeconomic system are examined in this study. The problem raised is how Abu Yusuf provides ideas and contributions of thought in the macroeconomic system through several approaches. The methodology uses a qualitative approach that involves a descriptive-analytical analysis of Abu Yusuf's works, especially his work entitled Kitab "al-kharaj" as well as related literature that discusses his contribution to Islamic economics. The findings of this study show that Abu Yusuf emphasizes aspects of income distribution, fiscal justice, efficiency in the use of public power, as well as the role of the state as a regulator and supervision, these ideas are relevant in answering the challenges of economic inequality and fiscal crisis.